FACTORS INFLUENCING A SCIENCE OF LEARNING TRAINING PROGRAM FOR SCHOOL TEACHERS IN EUROPE - Neto, Catarina; Beardsley, Marc; Silveira, Ana; Saar, Merike; Simić, Nataša (Revista de Produtos Educacionais e Pesquisas em Ensino, 2024)
This paper was developed as part of a Science of Learning training program during a 3-year European project and aims to identify factors that may be influencing the application of findings from the Science of Learning to teacher practice. Data from 298 schoolteachers was collected through a self-reported questionnaire applied in Portugal, Spain, Estonia, and Serbia, and is qualitatively refined with in-service teachers and trainers’ feedback on the factors influencing the feasibility and effects of the training program. The results presented to consider changes in teachers’ knowledge, skills and beliefs, and the changes in their students’ behavior and academic accomplishments, highlighting the evidence of the existence in teachers of beliefs and concerns that may interfere with effective Self-Regulated Learning instruction. This Contributions from this study intend to lay the ground for future research and interventions to support teachers, students, society, and government demystifying beliefs that are not consistent with Self-Regulated Learning.